SELECTION OF KPU AND BAWASLU MEMBERS: FIT AND PROPER TEST IN THE PERSPECTIVE OF ELECTION LAW AND MERITOCRACY - Nurfajila, Erina Fionita; Hurriyah Hurriyah (Politik Indonesia: Indonesian Political Science Review, 2024)
Commision II of DPR RI plays a crucial role in selecting election organizers at the national level by conducting a fit and proper test (FPT) process. The decisions and mechanisms of the FPT process directly affect the integrity of the election results. This research aims to identify aspects of political recruitment that are applied in the design of the FPT for prospective members of the Indonesian KPU and Bawaslu for the 2022-2027 period using qualitative descriptive methods and data collection techniques through literature studies and interviews. The results show that there is a gulf between the candidacy (candidates’ suitability) and selectorate (political actors) aspects, namely the involvement of political party members in the selectorate aspect, which leads to preferential selection guided by the interests of the political parties. In the technical and location aspect, the difficulty of access for candidates outside Jakarta, a lack of in-depth exposure to the FPT process, the absence of assessment instruments, and limited public involvement are obstacles in what should be a merit-based system in principle. This finding implies that the selected election organizers who are free from political interests are an anomaly in selection processes run by political institutions.